Instructor Toolkit - Values and Policy in Interdisciplinary Environmental Science: A Dialogue-based Framework for Ethics Education - Anonymous (Online Ethics Center, 2018)
The "Values and Responsibility in Interdisciplinary Environmental Science" curriculum (http://eese.msu.edu/) is a modular resource designed to be implemented by environmental science instructors who have no ethics training for the purpose of guiding students through an analytic examination of the values and policy dimensions of their environmental science context. With the support of the NSF (SBE-1338614, MSU; SBE-1338626, Oregon State University) and with guidance from a national survey of environmental science instructors (Hall, Troy E., et al. 2016), this dialogue-based curriculum enables students to reflect on values, policy, and responsibility in a way that is informed by case study work and appreciation for different disciplinary perspectives. At the heart of this curriculum is the Toolbox dialogue methodology " students are given the opportunity to develop their own dialogue structures via reflection on topics with ethical implications, e.g., expertise, risk, policy constraints, and non-human impacts.
Instructor Materials
Keywords: Collaboration; Environmental Justice; Interdisciplinary Research; Public and Community Engagement; Research and Practice; Risk; Sustainability